Further Remarks on Fixed-Point Theorems in the Context of Partial Metric Spaces - Mohamed Jleli; Erdal Karapınar; Bessem Samet (Abstract and Applied Analysis)
New fixed-point theorems on metric spaces are established, and analogous results on partial metric spaces are deduced. This work can be considered as a continuation of the paper Samet et al. (2013).